Atypical Event Profiling of Intra-Arterial Chemotherapy. (May 2022) - Bach, Austin; Villegas, Victor M.; Gold, Aaron S.; Murray, Timothy G.
Purpose: Three cases of atypical events following intra-arterial chemotherapy for the treatment of retinoblastoma are presented. Methods: Case report. Results: One patient had acute orbital swelling with proptosis, another with extravasation of the chemotherapeutic agent, and the final with total ipsilateral hearing loss. Conclusions: These cases underscore the importance of maintaining close follow-up when using intra-arterial chemotherapy for treatment of retinoblastoma.